2020
DOI: 10.31838/jcr.07.04.137
|View full text |Cite
|
Sign up to set email alerts
|

Iot Based Health Monitoring System

Abstract: Healthcare is given the extreme importance now a-days by each country with the advent of the novel corona virus. So in this aspect, an IoT based health monitoring system is the best solution for such an epidemic. Internet of Things (IoT) is the new revolution of internet which is the growing research area especially in the health care. With the increase in use of wearable sensors and the smart phones, these remote health care monitoring has evolved in such a pace. IoT monitoring of health helps in preventing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…IoT health screening aids in disease spread prevention as well as accurate evaluation of health status, regardless location of the doctor furthermore it is facilitating continuous health condition monitoring. The Remote Healthcare Monitoring arrangement enables patients to be observed outside of traditional hospital environments (for example, at home), and increases access to human resources offices while lowering costs [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IoT health screening aids in disease spread prevention as well as accurate evaluation of health status, regardless location of the doctor furthermore it is facilitating continuous health condition monitoring. The Remote Healthcare Monitoring arrangement enables patients to be observed outside of traditional hospital environments (for example, at home), and increases access to human resources offices while lowering costs [3].…”
Section: Introductionmentioning
confidence: 99%
“…In their research paper Valsalan, et al in 2020, suggested an IoT-based health tracking device with a mobile physiological screening mechanism that can continuously screen the patient's temperature, heartbeat and other specific necessary parameters. They suggested a continuous monitoring and control instrument to screen the patient status and archive the patient data in a server using a wi-fi based module remote communication [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase of average life expectancy, there is growing interest in maintaining healthy life. Particularly, various studies have been conducted to monitor healthrelated biosignals such as heart rate and breath rate using wearable devices and/or other remote medical diagnosis equipment [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Many medical errors occur because individuals are in the care of the patient or the elderly are dealing in large quantities of pills every day. This work includes creating the pillbox model using IoT and a smart health monitoring plan, design, and ADR security algorithm [1], [2]. This work is intended to address this shortcoming in the medical field.…”
Section: Introductionmentioning
confidence: 99%